Compras públicas sustentáveis no Centro Federal de Educação Tecnológica de Minas Gerais - Sousa, Jânio José De (2018)
Public institutions carry out purchases that are responsible for moving the volume of goods and that have an impact on environmental issues. In this sense, there is the Environmental Agenda in Public Administration - A3P which includes guidelines and programs with the objective of implementing, in the administrative and operational activities of the Government, a sustainable management. The A3P has specific guidelines for the theme "sustainable biddings" and they are related, by several authors, as of great importance in the quest for sustainability. In this way, public administration has implemented actions to give effect to the inclusion of criteria considered sustainable in its bidding documents. This time, the question arises: what sustainability criteria are being used by the Federal Center of Technological Education of Minas Gerais - CEFETMG in their purchasing processes? In order to respond to the questioning, this work proposed to analyze the bidding of CEFET-MG seeking to verify if sustainability criteria are being inserted in the bidding documents for the acquisition of goods and services, in the period of 2016 and 2017, based on a methodological project that had as reference other research already done on the subject. After analyzing the results, it was verified that the CEFET-MG presents sustainable practices still punctual. However, in general, it was evidenced that the organ has presented sustainable criteria in its edicts and the description of some items. It was verified the possibility of conducting bids on sustainable models such as the reality in other bodies. After that, it was suggested that CEFET-MG incorporate in its bids the practices adopted by these institutions, since they already adopt sustainable practices and criteria in their purchases.